Faktor Gejala dan Komorbid yang Berhubungan dengan Kematian Pasien COVID-19 di Tangerang Selatan, November 2020-Mei 2021 - Ade Ayu Lanniari Harahap; Helda Helda (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2023)
Background : Coronavirus disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The number of confirmed cases and deaths of COVID-19 continues to increase globally. Epidemiology and clinical characteristics of COVID-19 cases from Indonesia are scanty. High-quality evidence to understand the disease and can be used as a basis for policymaking. Therefore, this study was conducted to determine the symptom factors and comorbidities associated with mortality in COVID-19 patients in South Tangerang from November 2020 to May 2021.Methode : A Case-control study of confirmed cases of COVID-19 in South Tangerang. The cases included 337 COVID-19 patients who died and 347 controls who were still alive. Data on age, gender, symptoms, and comorbidities were collected through Epidemiological Surveillance (ES) of COVID-19 patients at the South Tangerang Health Office from November 2020 to May 2021 in association with death and analyzed using chi-square test and simple logistic regression.Result : The results of multivariate analysis showed that risk factors such as age (OR=5.059; 95% CI: 3.209-7.974), gender (OR=2.650; 95% CI: 1.758-3.996), fever symptoms (OR=0.499; 0.331- 0.753), co-morbidities with diabetes mellitus (OR=15.94; 95% CI: 7.397-34.350), hypertension (OR=4.005; 95% CI: 2.440-6.572), heart disease (OR=7.249; 95% CI: 2.893-18.162 ) and chronic kidney failure (OR=12,523, 95% CI: 1,571-99,808) had an influence on the incidence of death of COVID-19 positive patients in South Tangerang.ConclusionÂ : These findings indicate that older age, male gender, symptoms of fever, and comorbidities include a history of diabetes mellitus, hypertension, heart disease, and kidney failure due to the death of COVID-19 patients in South Tangerang. The need to enhance specific public health measures to reduce the risk of death in patients infected with COVID-19.